2020
DOI: 10.1093/aesa/saaa003
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Microbiota Between Two Multilocus Lineages of the Sugarcane Aphid (Melanaphis sacchari) in the Continental United States

Abstract: The sugarcane aphid (SCA), Melanaphis Sacchari (Zehntner) (Hemiptera: Aphididae), has been considered an invasive pest of sugarcane in the continental United States since 1977. Then, in 2013, SCA abruptly became a serious pest of U.S. sorghum and is now a sorghum pest in 22 states across the continental United States. Changes in insect-associated microbial community composition are known to influence host-plant range in aphids. In this study, we assessed whether changes in microbiota composition may explain th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 111 publications
(117 reference statements)
0
16
0
Order By: Relevance
“…While insect species was the strongest driver of structure and diversity of bacterial communities in this study, diet also showed a significative effect. Several previous studies showed that insect-associated microbial communities are often shaped by their host's diet, for example in termites (Mikaelyan et al, 2015), aphids (Wu et al, 2018;Xu et al, 2019Xu et al, , 2020Holt et al, 2020), bugs (Martinez et al, 2019), beetles (Kim et al, 2017), fruit flies (Malacrinò et al, 2018;Majumder et al, 2019;Woruba et al, 2019;Asimakis et al, 2019), soldier flies (Bruno et al, 2019) and ants (Russell et al, 2009). Interestingly, the bacterial communities associated with Phtorimaea operculella varied even according to the plant tissue insects were feeding on (Zheng et al, 2020).…”
Section: Response Of Bacterial Clades To Factors Influencing Insect Microbial Communitiesmentioning
confidence: 99%
“…While insect species was the strongest driver of structure and diversity of bacterial communities in this study, diet also showed a significative effect. Several previous studies showed that insect-associated microbial communities are often shaped by their host's diet, for example in termites (Mikaelyan et al, 2015), aphids (Wu et al, 2018;Xu et al, 2019Xu et al, , 2020Holt et al, 2020), bugs (Martinez et al, 2019), beetles (Kim et al, 2017), fruit flies (Malacrinò et al, 2018;Majumder et al, 2019;Woruba et al, 2019;Asimakis et al, 2019), soldier flies (Bruno et al, 2019) and ants (Russell et al, 2009). Interestingly, the bacterial communities associated with Phtorimaea operculella varied even according to the plant tissue insects were feeding on (Zheng et al, 2020).…”
Section: Response Of Bacterial Clades To Factors Influencing Insect Microbial Communitiesmentioning
confidence: 99%
“…shows diet breadth is linked to microbiome diversity and community structure [21]. Previous research also indicates the composition of aphid microbial communities are structured by host plant [11,15,16,20,22,24,43,44] and heritable bacterial symbionts are involved in expanding diet breadth [23,25].…”
Section: Discussionmentioning
confidence: 97%
“…Microbes are also hypothesized to contribute to variation in the capacity of insect herbivores to consume chemically defended plants [8]. Finally, feeding on different host plants can in uence the composition of microbial communities associated with insect herbivores [11,14,19,20]. However, aside from a handful of wellcharacterized nutritional symbionts it is unclear to what extent insect microbial communities either directly or indirectly contribute to host plant adaptation and diet breadth.…”
Section: Introductionmentioning
confidence: 99%
“…Characterizing genetically differentiated populations is not only important for assessing patterns of partial reproductive isolation and therefore gene drive speed of spread, but also because genetically differentiated populations may vary in traits relevant to pest control (Medina, 2012;Araya-Anchetta et al, 2015). For example, genetically differentiated populations have been found to differ in several traits relevant to pest control, such as insecticide resistance (Nauen & Denholm, 2005;Carletto et al, 2010), cold hardiness (Broberg et al, 2018), diapause timing (Boivin et al, 2004;Dambroski & Feder, 2007), number of generations per season (Boivin et al, 2004), host plant resistance (Hanson et al, 2018), host preference (Linn et al, 2003), host range (Feder et al, 1988;Peccoud et al, 2009), vector competence (Boukari et al, 2020), microbiota composition (Medina et al, 2011;Holt et al, 2020), and susceptibility to natural enemies (Hufbauer & Via, 1999;Martinez et al, 2014). Similarly, genetically differentiated pest populations may show different degrees of gene drive resistance.…”
Section: Host-associated Differentiation May Influence Gene Drive Speed Of Spreadmentioning
confidence: 99%